Research on Surrounding Rock Stability Affected by Surrounding Rock Pressure and Rock Fracture under Blasting Vibration Load Action - Qingjie Qi; Shuai Huang; Yingjie Liu (Advances in Civil Engineering)
The influence mechanisms of factors, such as high confining pressure and in situ stress caused by deep mining on the stability of surrounding rock of roadways, are complex. Particularly, the motion and energy release of the rock mass medium can be caused by vibration transmission induced by blasting excavation in the underground mining. Based on this, by taking a metal mine with the buried depth of 498 m as a research object, influences of different excavation distances on roof deformation and stress of roadway surrounding rock during the excavation were studied by using a three-dimensional numerical model. Moreover, the weak position of the roof of surrounding rock was determined. Finally, influences of fractured rock mass on propagation of blasting vibration waves in surrounding rock and energy distribution characteristics were analyzed. The research shows that rock mass around the excavated roadway moves towards the excavated space in different advance stages of a working face. The displacement fields on the top of a lateral tunnel present a heart-shaped distribution along the working face and the maximum displacement appears to the roof at the junction of the lateral tunnel and a horizontal roadway along veins. As the advance distance of the working face increases, compression-shear failure mostly occurs in the roadway surrounding rock, and tensile failure and combined tensile and shear failure occur at the unsupported roof and floor of the roadway. With the rise of the confining pressure, the total energy in frequency bands increases and its increase amplitude also rises. Furthermore, energy in a frequency domain of response signals to blasting vibration is transmitted from a secondary frequency band to a primary frequency band and is increasingly concentrated. With the increase of the damage degree of the roadway, signal energy in the frequency domain is transmitted from the primary to the secondary frequency band and signal energy is distributed more dispersedly. The test results are basically consistent with numerical simulation results. This study could provide technical guidance for the stability evaluation of surrounding rock of underground engineering structures.